2002
DOI: 10.1515/9783110936018
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Poisson Models and their Applications in Insurance and Finance

Abstract: Preface xiii 1 Basic notions of probability theory 1 1.1 Random variables, their distributions and moments 1 1.2 Generating and characteristic functions 11 1.3 Random vectors. Stochastic independence 21 1.4 Weak convergence of random variables and distribution functions ... 24 1.5 Poisson theorem 30 1.6 Law of large numbers. Central limit theorem. Stable laws 35 1.7 The Berry-Esseen inequality 45 1.8 Asymptotic expansions in the central limit theorem 47 1.9 Elementary properties of random sums 56 1.10 Stochast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 0 publications
0
100
0
6
Order By: Relevance
“…For an overview on Cox processes and their applications to actuarial and financial mathematics, we refer the reader to Grandell (1976) and Bening and Korolev (2002); see also Korolev (1999Korolev ( , 2001. In this subsection we prove that the precise large-deviation result obtained in Theorem 4.1 can be applied to the compound process…”
Section: Doubly Stochastic Counting Processmentioning
confidence: 74%
“…For an overview on Cox processes and their applications to actuarial and financial mathematics, we refer the reader to Grandell (1976) and Bening and Korolev (2002); see also Korolev (1999Korolev ( , 2001. In this subsection we prove that the precise large-deviation result obtained in Theorem 4.1 can be applied to the compound process…”
Section: Doubly Stochastic Counting Processmentioning
confidence: 74%
“…Many authors have contributed to the asymptotic theory of sums, maxima, and general random sequences with a random number of terms. See, for example, Korolev (1994Korolev ( , 1995, the books of Kruglov and Korolev (1990), Bening and Korolev (2002), and the references therein. Here, however, our focus is on convergence of processes and their connections to fractional calculus.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional differential equations are useful to model various problems in physics (see a comprehensive review by Metzler and Klafter, 2004), finance (see a recent review by Scalas, 2006), and hydrology Benson et al, 2001Benson et al, , 2000Schumer et al, 2001). Time-fractional derivatives are connected with physical models of particle sticking and trapping .…”
Section: Introductionmentioning
confidence: 99%
“…where the event arrival rate r is itself a time dependent random process independent of N (t) [3]. Bezrukov and Vodyanoy have shown that the following arrival rate r(t) of a doubly stochastic Poisson process exhibits SR:…”
Section: Non-dynamical Stochastic Resonancementioning
confidence: 99%